Delphi expert consensus on phlebotomy limitations and treatment challenges in HFE -related hemochromatosis - Jeremy Shearman; Domenico Girelli; Dominik J. Schaer; Sant-Rayn Pasricha; Kris V. Kowdley; John K. Olynyk; Gregory J. Kato; Sonya Abraham; Soraya Benchikh El Fegoun; Charlotte Pollet; Uta Merle (Clinical Hematology International, 2026)
HFE -related hemochromatosis (HC) is caused by hepcidin dysregulation and is characterized by excessive iron absorption and accumulation in the liver, heart, and endocrine glands, which leads to complications including arthropathy, cirrhosis, and hepatocellular carcinoma. Standard of care (SoC) typically involves phlebotomy, with iron chelators used less frequently. However, these therapies may cause side effects and negatively impact quality of life, making them troublesome for some patients. Using the Delphi methodology, a survey was developed to identify unmet needs and clinical challenges within the current therapeutic landscape of HC, and to establish consensus statements for its management. Consensus was defined as ≥75% agreement. Thirty-two HC specialists from Europe, Australia and the USA responded to the survey. After three rounds of survey refinement, final consensus statements were compiled. The Delphi process identified key unmet needs in HC, including lack of alternatives to phlebotomy, persistent symptoms, and burden related to the use of current SoC. The consensus process helped establish definitions for high phlebotomy treatment burden, intolerance, and suboptimal response to phlebotomy. The process also identified the subgroup of patients overly burdened by phlebotomy. Patient-reported outcomes were considered key to assessing phlebotomy’s impact, although they are rarely measured in clinical practice. The Delphi study highlighted the limitations of phlebotomy, with respondents identifying a high unmet need for patients who cannot be managed with or do not tolerate this approach. The study suggested exploring alternative therapy options for patients who experience high treatment burden or intolerance to phlebotomy.